2021
DOI: 10.1002/cjoc.202100022
|View full text |Cite
|
Sign up to set email alerts
|

A Cost‐Effective D‐A‐D Type Hole‐Transport Material Enabling 20% Efficiency Inverted Perovskite Solar Cells

Abstract: Energy conversion | Donor-acceptor systems | Interfaces | Hole-transport materials | Inverted perovskite solar cells High-performance, cost-effective hole-transport materials (HTMs) are greatly desired for the commercialization of perovskite solar cells (PVSCs). Herein, two new HTMs, TPA-FO and TPA-PDO, are devised and synthesized, which have a donor-acceptor-donor (D-A-D) type molecule design featuring carbonyl group-functionalized arenes as the acceptor (A) units. The carbonyl group at the central core of HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Furthermore, the time‐resolved photoluminescence (TRPL) spectra (Figure 2d) have been also employed to deeply understand the dynamics of charge recombination. [ 53 ] As shown from Table S2, it is observed that TIPS‐PEN incorporated perovskite shows a shorter average lifetime (13.51 ns) compared with the control (35.32 ns), indicating that the photoexcited carriers can be extracted rapidly and thus efficiently inhibit charge carrier recombination. To further elucidate more directly the defect passivation effect of TIPS‐PEN and the more effective charge extraction at the perovskite/HTL interface, the space charge‐limited current (SCLC) measurements are conducted to calculate the trap density and carrier mobility under dark conditions (Figure 2e and Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the time‐resolved photoluminescence (TRPL) spectra (Figure 2d) have been also employed to deeply understand the dynamics of charge recombination. [ 53 ] As shown from Table S2, it is observed that TIPS‐PEN incorporated perovskite shows a shorter average lifetime (13.51 ns) compared with the control (35.32 ns), indicating that the photoexcited carriers can be extracted rapidly and thus efficiently inhibit charge carrier recombination. To further elucidate more directly the defect passivation effect of TIPS‐PEN and the more effective charge extraction at the perovskite/HTL interface, the space charge‐limited current (SCLC) measurements are conducted to calculate the trap density and carrier mobility under dark conditions (Figure 2e and Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Guo and co-workers prepared two D-A-D type linear small molecule HTMs featuring carbonyl group-functionalized arenes as the acceptor units and MeO-TPA groups as the donor units, denoted as TPA-FO and TPA-PDO. 160 Compared with one carbonyl group functionalized TPA-FO, TPA-PDO containing two carbonyl groups possessed lower hole mobility, stronger wettability harmful for perovskite crystal growth, and weaker interaction with Pb 2+ without the chelation effect. 161 As a result, the dopant-free TPA-FO-based PSCs exhibited an excellent PCE of 20.2%, while the device based on TPA-PDO only gave an inferior PCE of 17.0%.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 98%
“…Also on p‐i‐n PSCs, Guo's group designed and synthesized two new HTMs ( TPA‐FO and TPA‐PDO ) with carbonyl as the central atom. [ 33 ] The carbonyl groups of TPA‐FO and TPA‐PDO could not only improve the surface wettability and adjust the frontier molecular orbital energy level, but also achieve effective surface passivation effect to reduce the recombination loss. The dopant‐free TPA‐FO with one carbonyl group produced a high PCE of 20.24%, while its cost was as low as $30 g –1 by a simple one‐step synthesis process.…”
Section: Dopant‐free Organic Small Molecular Htmsmentioning
confidence: 99%